2022
DOI: 10.1371/journal.pone.0275097
|View full text |Cite
|
Sign up to set email alerts
|

Femoral fixation methods for hamstring graft in anterior cruciate ligament reconstruction: A network meta-analysis of controlled clinical trials

Abstract: Objective To compare the clinical effectiveness of cortical button (CB), cross-pin (CP) and compression with interference screws (IS) fixation techniques in anterior cruciate ligament (ACL) reconstruction using hamstring graft. Methods Studies were systematically retrieved from PubMed, Embase, Cochrane Library and Web of Science up to May 20, 2021. Primary outcomes were KT-1000 assessment, International Knee Documentation Committee (IKDC) score A or B, Lachman’s test, pivot-shift test, visual analogue scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…At this point, there is no clear consensus regarding the “best” graft fixation method, as each option has advantages and disadvantages. Several recent meta-analyses [ 20 , 24 , 53 , 82 , 106 ] and network meta-analyses [ 53 , 129 ] have demonstrated no superiority in clinical or patient-reported outcomes (PROs) of any particular fixation method. However, a recent meta-analysis of 40 studies found improved arthrometric stability and fewer graft ruptures but no difference in PROs using suspensory- compared to interference screw fixation for quadrupled HT autograft [ 15 ].…”
Section: Graft Fixationmentioning
confidence: 99%
“…At this point, there is no clear consensus regarding the “best” graft fixation method, as each option has advantages and disadvantages. Several recent meta-analyses [ 20 , 24 , 53 , 82 , 106 ] and network meta-analyses [ 53 , 129 ] have demonstrated no superiority in clinical or patient-reported outcomes (PROs) of any particular fixation method. However, a recent meta-analysis of 40 studies found improved arthrometric stability and fewer graft ruptures but no difference in PROs using suspensory- compared to interference screw fixation for quadrupled HT autograft [ 15 ].…”
Section: Graft Fixationmentioning
confidence: 99%
“…In practice, RigidFix cross pins have been used for femoral tunnel fixation widely and achieved satisfactory results. 11,27,[32][33][34][35][36] Persson et al found that RigidFix had a lower risk of revision compared with the Endobutton. 34 Snaebjörnsson et al's study also showed the RigidFix cross pins system entailed a lower risk of ACL revision compared with other femoral fixations.…”
Section: Rigidfix Cross Pins Advantage In Aclrmentioning
confidence: 99%
“…8 In addition, successful ACLR requires graft stability in the immediate postoperative period 9 and tendon-bone healing in the anatomic tunnel. 10,11 This is especially true for the tibial graft fixation, which has been considered the weakest link of the reconstruction 12 due to the lower density of the tibial bone and the parallel graft-fixation associated with the tunnel. 13 The tibial grafts are usually fixed with interference screws 14,15 as they were easy to place, however the tibial interference screws sometimes have complications such as slippage and cysts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations